Graduated compression and its relation to venous refilling time. Issue 6606 (31st October 1987) - Cornwall, J V; Doré, C J; Lewis, J D
Abstract : Graduated compression is important in improving venous function, but the pressure profiles of different brands of stockings in situ and effects on a direct measure of venous function have not been investigated. The pressure profiles of 15 different types of below knee compression stockings were established with a medical stocking tester in 13 healthy volunteers. Analysis of variance was performed for each stocking separately, considering the factors of size of stocking, site of measurement, and their interaction. The criteria used to define satisfactory function were that the stockings should have a significant linear trend with site--that is, graduation--and no other significant effects. Only five types of stockings met these standards. Venous function was then assessed by photoplethysmography in 19 patients with defined venous abnormalities. For each patient the effect on venous refilling time of three satisfactory and three unsatisfactory stockings was assessed. The three satisfactory stockings gave refilling times that were not significantly different from normal in patients with both superficial and deep vein incompetence, while refilling times with the three unsatisfactory stockings remained significantly below normal in all patients with deep vein incompetence; one stocking had no significant effect on refilling times in either group. Functional testing of compression hosiery should form part of future British Standards specifications.